(untitled) (International journal of artificial intelligence, 2024)
Digital transformation has risen as a significant imperative in the current world economy as a catalyst of change. Taking AI, blockchain and IoT as examples, more and more organizations are embracing these digital technologies to optimize operations, improve customer satisfaction and open up new sources of revenues. This article discusses how digitation can be effective and looks at some of the issues surrounding it as well. Even if there are certain challenges like high cost, organizational resistance and cybersecurity threats, strategic planning and organizational commitment to change are effective antidotes to these challenges. In line with this research approach, this study through a synthesis of secondary data and case studies stresses the need for organizations to ensure their digitization strategies are serving long-term business development goals of attaining sustainable growth and competitiveness in the evolving market.